RISK FACTORS FOR ABORTION IN KELIAT PERAK HOSPITAL, DELI SERDANG REGENCY, NORTH SUMATRA PROVINCE IN 2024 - Kristiani Hulu, Vian; Aprianti, Yunita; Ritonga, Yesika; Julaiha; Simamora, Lasria (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Abortion is the spontaneous termination of pregnancy before reaching 20 weeks of gestation, and is a crucial reproductive health issue in Indonesia. At Keliat General Hospital, Deli Serdang Regency, there are reports of spontaneous abortion cases frequently experienced by pregnant women.Pourpose : This study aims to examine the risk factors associated with abortion incidents at Keliat General Hospital, Deli Serdang Regency, North Sumatra Province.Method: This quantitative study applies an observational analytical approach with a case-control study design. The study sample consisted of 60 respondents, divided into 30 people in the case group (mothers who experienced abortion) and 30 people in the control group (mothers who did not experience abortion). Data collection was carried out retrospectively through medical records using a structured questionnaire. Data analysis: included univariate analysis and bivariate analysis using the Chi-Square statistical test (alpha = 0.05). Result :Bivariate analysis indicated that age had a significant correlation with the incidence of abortion (p = 0.007; OR = 4.57), indicating that mothers in the high age category (35 years) were at 4.5 times higher risk of abortion. Furthermore, anemia also showed a statistically significant correlation (p = 0.018; OR = 3.59), indicating that pregnant women with anemia were more likely to experience miscarriage. On the other hand, parity (p = 0.605) and history of previous abortion (p = 0.371) showed p values > 0.05, indicating no significant association with the incidence of abortion in the study area.Conclusion: Extreme maternal age (high risk) and anemia are important risk factors directly related to the incidence of abortion at Keliat General Hospital. Therefore, it is necessary to improve the quality of antenatal care, early detection of at-risk ages, and optimization of screening programs and anemia management from the beginning of pregnancy to reduce the potential for spontaneous miscarriage in pregnant women.